Ischemic Stroke and TIA in Young Adults - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at the Massachusetts General Hospital, Boston, MA studied retrospectively the risk factors and yield of diagnostic tests, neuroimaging findings, and treatment of ischemic strokes in 215 consecutive young adult patients (aged 18 to 45 years) seen between 2005 and 2010.